Prefrontal Glutamate Neurotransmission in PTSD: A Novel Approach to Estimate Synaptic Strength in Vivo in Humans. (April 2022) - Averill, Lynnette A.; Jiang, Lihong; Purohit, Prerana; Coppoli, Anastasia; Averill, Christopher L.; Roscoe, Jeremy; Kelmendi, Benjamin; De Feyter, Henk M.; de Graaf, Robin A; Gueorguieva, Ralitza; Sanacora, Gerard; Krystal, John H.; et al.
Background: Trauma and chronic stress are believed to induce and exacerbate psychopathology by disrupting glutamate synaptic strength. However, in vivo in human methods to estimate synaptic strength are limited. In this study, we established a novel putative biomarker of glutamatergic synaptic strength, termed energy-per-cycle (EPC). Then, we used EPC to investigate the role of prefrontal neurotransmission in trauma-related psychopathology. Methods: Healthy controls (n = 18) and patients with posttraumatic stress (PTSD; n = 16) completed 13 C-acetate magnetic resonance spectroscopy (MRS) scans to estimate prefrontal EPC, which is the ratio of neuronal energetic needs per glutamate neurotransmission cycle (VTCA /VCycle ). Results: Patients with PTSD were found to have 28% reduction in prefrontal EPC ( t = 3.0; df = 32, P = .005). There was no effect of sex on EPC, but age was negatively associated with prefrontal EPC across groups ( r = –0.46, n = 34, P = .006). Controlling for age did not affect the study results. Conclusion: The feasibility and utility of estimating prefrontal EPC using 13 C-acetate MRS were established. Patients with PTSD were found to have reduced prefrontal glutamatergic synaptic strength. These findings suggest that reduced glutamatergic synaptic strength may contribute to the pathophysiology of PTSD and could be targeted by new treatments.